Respuesta :

Answer:

  • [tex]g(4) = -11[/tex]
  • [tex]h(4) = 43[/tex]

Step-by-step explanation:

Given the functions

[tex]g(x)=-2x-3[/tex]

[tex]h(x)=7x+15[/tex]

  • Evaluating [tex]g(x)=-2x-3[/tex] at x=4

putting x = 4

[tex]g(x)=-2x-3[/tex]

[tex]g(4) = -2(4)-3[/tex]

[tex]g(4) = -8-3[/tex]

[tex]g(4) = -11[/tex]

Therefore,

at x = 4, g(4) = -11

  • Evaluating [tex]h(x) = 7x + 15[/tex] at x = 4

Putting x = 4

[tex]h(x) = 7x + 15[/tex]

[tex]h(4) = 7(4) + 15[/tex]

[tex]h(4) = 28+15[/tex]

[tex]h(4) = 43[/tex]

Therefore,

at x = 4, h(4) = 43

ACCESS MORE